Carcass Characteristics, Haematology, Serum Chemistry and Enzymes in Broiler Chickens Fed Maggot Meal as a Protein Substitute for Fishmeal. (Global Journal of Medical Research, 2019)
Conventional protein sources used in poultry farming are extensively competed for, by livestock and humans leading to high prices and reduced returns. Focus on better utilization of available alternative feed resources with little or no negative impacts on the health of broilers and consumers is useful. The objective of this research was to assess the performance of carcass characteristics, hematology, serum chemistry, and enzymes in broiler chickens fed maggot meal as a protein substitute for fishmeal. 225 Tropical Broc day old chicks brooded for two weeks and fed the control diet, were distributed in a completely randomized block design with five treatments and three replicates each consisting of the starter and finisher phases and the experiment conducted for eight weeks. Diets were compounded with maggot meal (MM) replacing FM at 0%, 25%, 50%, 75% and 100%.
Keywords: maggot meal; hematology; serum chemistry; enzymes; carcass characteristics